The effect of squat thrust, sit-up, and power leg exercises on football heading ability in 13-year-old students at persopi elang timur football academy - Wawan Nur Rohman; Syamsuryadin, Syamsuryadin; Ibnu Danang Pratama; Abyan Aufa Al Hanif; Haziq Hanantoseno Maramis; Hassan Naufal Yahya; Rouf Azzam Rozaq; Muhammad Aulia Wirawan; Rafi Fadhil Asmi; Thoriq Arkanudin; Fathiya Salsabila Nur Aini (Jorpres (Jurnal Olahraga Prestasi), 2022)
The objective of this research is to determine the effect of squat-thrust, sit-up, and leg power training towards the football heading ability of SSB Persopi ELTI (Persopi ELTI Football School) students in the age group of 13 years old. The heading ability must be possessed by every football player to attack and defend. This research was an experimental study with a squat pretest-posttest design. The research population included all SSB Persopi ELTI players in the age group of 13 years old totaling 24 students. The sampling technique was total sampling with the ordinal pairing division method. The research instrument was a heading test with a validation and reliability level of 0.746 and 0.818 while to analyze the data using the t-test. Based on the research findings, there is a significant effect of training with squat-thrust, sit-up, and leg power on the heading ability of SSB Persopi Elang Timur students in the age group of 13 years old. If you look at the mean difference at 1.66 where the mean pretest jump heading is at 2.50 and the posttest jump heading increases at 3.58. And the pretest normal heading is at 3.08 and the posttest normal heading increases at 5.42. Hence, it can be concluded that training with squat thrust, sit ups, and leg power contributes positively to improving the heading ability. This difference reflects an increase in jump heading at 66.68% while for normal heading at 54.12%. While for the control group, the pretest jump heading is at 1.8 and the posttest jump heading is at 2.17 and the pretest normal heading is at 2.42 and the posttest normal heading is at 3.50.